Deciphering diet and monitoring movement: Multiple stable isotope analysis of the viking age settlement at Hofstaðir, Lake Mývatn, Iceland. Issue 1 (22nd January 2016) - Sayle, Kerry L.; Hamilton, W. Derek; Cook, Gordon T.; Ascough, Philippa L.; Gestsdóttir, Hildur; McGovern, Thomas H.
ABSTRACT: Objectives: A previous multi‐isotope study of archaeological faunal samples from Skútustaðir, an early Viking age settlement on the southern shores of Lake Mývatn in north‐east Iceland, demonstrated that there are clear differences in δ 34 S stable isotope values between animals deriving their dietary protein from terrestrial, freshwater, and marine reservoirs. The aim of this study was to use this information to more accurately determine the diet of humans excavated from a nearby late Viking age churchyard. Materials and Methods: δ 13 C, δ 15 N, and δ 34 S analyses were undertaken on terrestrial animal ( n  = 39) and human ( n = 46 ) bone collagen from Hofstaðir, a high‐status Viking‐ period farmstead ∼10 km north‐west of Skútustaðir. Results: δ 34 S values for Hofstaðir herbivores were ∼6‰ higher relative to those from Skútustaðir (δ 34 S: 11.4 ± 2.3‰ versus 5.6 ± 2.8‰), while human δ 13 C, δ 15 N, and δ 34 S values were broad ranging (−20.2‰ to −17.3‰, 7.4‰ to 12.3‰, and 5.5‰ to 14.9‰, respectively). Discussion: Results suggest that the baseline δ 34 S value for the Mývatn region is higher than previously predicted due to a possible sea‐spray effect, but the massive deposition of Tanytarsus gracilentus (midges) (δ 34 S: −3.9‰) in the soil in the immediate vicinity of the lake is potentially lowering this value. Several terrestrial herbivores displayed higher bone collagen δ 34 S values than their contemporaries, suggesting trade and/or movement of animals to the region from coastal areas. Broad ranging δ 13 C, δ 15 N, and δ 34 S values for humans suggest the population were consuming varied diets, while outliers within the dataset could conceivably have been migrants to the area. Am J Phys Anthropol 160:126–136, 2016. © 2016 Wiley Periodicals, Inc.